2014
DOI: 10.1111/jop.12247
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐epithelially entrapped blood vessels in ameloblastoma

Abstract: Although rare in occurrence, identification of IEBVs in ameloblastoma could potentially represent a new paradigm for vascular assessment of this neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Wnts and their DKK antagonists regulate the morphology of ectodermal organs (17)(18)(19)(20). Wnt10b is a canonical Wnt member (21) that is expressed during hair induction and hair reconstitution (22,23). Recent studies have shown that adenovirus-mediated Wnt10b expression (AdWnt10b) leads to epithelial and melanocyte cell differentiation and elongated hair shafts (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Wnts and their DKK antagonists regulate the morphology of ectodermal organs (17)(18)(19)(20). Wnt10b is a canonical Wnt member (21) that is expressed during hair induction and hair reconstitution (22,23). Recent studies have shown that adenovirus-mediated Wnt10b expression (AdWnt10b) leads to epithelial and melanocyte cell differentiation and elongated hair shafts (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%